The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1039/an9891401323
|View full text |Cite
|
Sign up to set email alerts
|

Masking agents in the spectrophotometric determination of metal ions with 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol and non-ionic surfactant

Abstract: Efficient masking methods were found for the selective spectrophotometrk determination of metal ions with 2-(5-bromo-2-pyridylazo)-5-diethylaminophenol in a micellar solution of a non-ionic surfactant. N-( Dithiocarboxy)sarcosine (DTCS) and nitrilotriacetic acid were good choices for the determination of iron(l1). Triethylenetetraamine and DTCS (or dimercaptosuccinic acid and diethylenetriamine) were an excellent combination for the specific determination of manganese(l1). A combination of pyrophosphate and et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 0 publications
0
15
0
1
Order By: Relevance
“…Due to strict regulations, nonionic surfactants have only limited application in the food industry, where they are employed to change the stability of various emulsions (18) and to decrease the retrogradation of amylopectin (19). Nonionic surfactants also have been used in analytical chemistry to increase the fluorescence of dansylated amino acids (20), improve protein separation in capillary zone electrophoresis (21), and mask side effects in spectrophotometry (22).…”
mentioning
confidence: 99%
“…Due to strict regulations, nonionic surfactants have only limited application in the food industry, where they are employed to change the stability of various emulsions (18) and to decrease the retrogradation of amylopectin (19). Nonionic surfactants also have been used in analytical chemistry to increase the fluorescence of dansylated amino acids (20), improve protein separation in capillary zone electrophoresis (21), and mask side effects in spectrophotometry (22).…”
mentioning
confidence: 99%
“…2-(5-Bromo-2-pyridylazo)-5-diethylaminophenol, 5-Br-PADAP or HL, has been used to detect trace amounts of various metal elements [15,16]. Its metal complexes have relatively high molar absorptivity in visible region.…”
Section: Watarai Et Al Clarified the Contribution Of Interfacial Commentioning
confidence: 99%
“…8,21 A complemental study revealed that cobalt(II) ions are not retained in a column loaded with TAC in the presence of reducing agents, such as ascorbic acid and hydroxylammonium chloride. In aqueous solution the cobalt(III) complex has green coloration and an absorption maximum at 576 nm.…”
Section: Complex Formation Studiesmentioning
confidence: 99%